2004
DOI: 10.1136/gut.2003.035451
|View full text |Cite
|
Sign up to set email alerts
|

Association between a functional polymorphism in the serotonin transporter gene and diarrhoea predominant irritable bowel syndrome in women

Abstract: Background and aims: Serotonin (5-hydroxtryptamine, 5-HT) is an important factor in gut function, playing key roles in intestinal peristalsis and secretion, and in sensory signalling in the brain-gut axis. Removal from its sites of action is mediated by a specific protein called the serotonin reuptake transporter (SERT or 5-HTT). Polymorphisms in the promoter region of the SERT gene have effects on transcriptional activity, resulting in altered 5-HT reuptake efficiency. It has been speculated that such functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
131
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(151 citation statements)
references
References 62 publications
(24 reference statements)
14
131
0
6
Order By: Relevance
“…It seems that early life experiences interact with some biologic and personality susceptibilities leading to the development of these disorders. A polymorphism in the serotonin reuptake transporter gene associated with fibromyalgia and affective or anxiety disorders has been suggested to be related with diarrhea predominant IBS (24). Finding OCD and depression as the most frequent psychiatric disorders among patients with functional bowel disease in the present study may be a support for this theory as both of these mood disorders are related to dysfunctions of serotonergic system.…”
Section: Discussionsupporting
confidence: 73%
“…It seems that early life experiences interact with some biologic and personality susceptibilities leading to the development of these disorders. A polymorphism in the serotonin reuptake transporter gene associated with fibromyalgia and affective or anxiety disorders has been suggested to be related with diarrhea predominant IBS (24). Finding OCD and depression as the most frequent psychiatric disorders among patients with functional bowel disease in the present study may be a support for this theory as both of these mood disorders are related to dysfunctions of serotonergic system.…”
Section: Discussionsupporting
confidence: 73%
“…However, there are other studies reporting a significant association between IBS-D and the S/S genotype. 34,35 An Indian study demonstrated that the frequency of SLC6A4 S/S genotype was higher in IBS-D than IBS-C, IBS-M and controls. 36 These genotypic results were different from our study, but taking the serotonin level and its association on subtypes into consideration, they might be in line with our study at least in part.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships between genes and digestive functions have been extensively studied using knockout animals (Choi et al, 2007) or polymorphism genotyping (Yeo et al, 2004). Very few studies have been conducted using genetic lines selected on quantitative digestive parameters.…”
Section: Discussionmentioning
confidence: 99%